2009
DOI: 10.1103/physrevb.80.081402
|View full text |Cite
|
Sign up to set email alerts
|

Fermi energy dependence of theG-band resonance Raman spectra of single-wall carbon nanotubes

Abstract: The Fermi energy dependence of the G-band resonance Raman spectra of single-wall carbon nanotubes ͑SWNTs͒ is calculated, including the Kohn anomaly effect for metallic tubes. The gate voltage dependence of the G-band Raman spectra for SWNTs shows chirality-dependent G + / G − spectra, reflecting their dependence on the eigenvector direction of the optical ͑LO and TO͒ phonon modes and the nanotube chirality. The G-band Raman spectra of single-wall carbon nanotubes ͑SWNTs͒ arise from the first-order, one-phonon,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 25 publications
5
41
0
Order By: Relevance
“…27,87,91,[137][138][139][140] The absence of the LO phonon feature for armchair tubes is consistent with some theoretical studies (e.g., References 27 and 145), i.e., it is not Raman active in armchair SWCNTs (although this still does not eliminate the presence of a Kohn anomalyonly its Raman activity), while it is inconsistent with more recent theories. 90,146 In conclusion, using resonant Raman measurements of macroscopic ensembles of ν = 0 enriched SWCNT samples, we have demonstrated that the appearance of a broad G − peak is due to the presence of non-armchair "metallic" tubes. More importantly, the G-band of the truly gapless armchair tubes consists of a single, narrow G + component and serves as a further diagnostic for their identification.…”
Section: G-band Raman Signatures Of Armchair and Non-armchair ν mentioning
confidence: 99%
See 1 more Smart Citation
“…27,87,91,[137][138][139][140] The absence of the LO phonon feature for armchair tubes is consistent with some theoretical studies (e.g., References 27 and 145), i.e., it is not Raman active in armchair SWCNTs (although this still does not eliminate the presence of a Kohn anomalyonly its Raman activity), while it is inconsistent with more recent theories. 90,146 In conclusion, using resonant Raman measurements of macroscopic ensembles of ν = 0 enriched SWCNT samples, we have demonstrated that the appearance of a broad G − peak is due to the presence of non-armchair "metallic" tubes. More importantly, the G-band of the truly gapless armchair tubes consists of a single, narrow G + component and serves as a further diagnostic for their identification.…”
Section: G-band Raman Signatures Of Armchair and Non-armchair ν mentioning
confidence: 99%
“…Returning to the G-band mode, experimental studies by Wu et al, 87 Telg et al, 88 Fouquet et al, 89 Michel et al, 77 and Park et al 90 attempted to correlate G-band line shape with specific (n, m), especially in light of a new explanation for the origin of the broad G − feature in metallic nanotubes as arising from the Kohn anomaly 91 (discussed later in Section VII). Raman measurements were made on individual, (n, m)-identified tubes.…”
Section: B Resonant Raman Scatteringmentioning
confidence: 99%
“…Recently, Sasaki et al (2010) showed that the phonon softening effect of the G can characterize the graphene edge structure. In the presence of free electrons, the G band and the radial breathing mode (RBM) phonon in single-walled carbon nanotubes (SWNTs) becomes soft as a function of the Fermi energy position, through an effect which is known as the Kohn anomaly (Sasaki et al 2008a,b;Farhat et al 2009;Kalbac et al 2009;Park et al 2009). These phenomena occur preferentially at graphene edges, since the electron wave function forms a standing wave by mixing elastically scattered waves at the edge where the momentum along the edge (perpendicular to the edge) is conserved (changes its sign).…”
Section: Defect-induced Selection Rules: Dependence On the Edge Atomimentioning
confidence: 99%
“…The various changes in the Raman spectra due to doping include differences in the intensity ratios between the G -and G + peaks, broadening/stiffening of the peaks, and frequency shifts. 14,16,26 Moreover, the asprepared SWNT bundles contain a mixture of semiconducting and metallic SWNTs, …”
mentioning
confidence: 99%
“…8,9 Raman spectroscopy is a powerful tool that has been used extensively to study charge transfer in SWNTs and in graphene. [10][11][12][13][14][15][16][17][18][19] Adsorption of electron donating and accepting molecules cause shifts in the Raman peak frequencies, which are proportional to the amount of carriers injected. 10 While charge transfer in SWNTs and graphene due to molecular dopants has been studied separately, there is very little work on the electronic interaction between SWNTs and graphene.…”
mentioning
confidence: 99%